Challenges associated with interfacing computed tomography to a picture archiving and communication system at the Baltimore Veterans Affairs Medical Center—A historical perspective - Kuzmak, Peter M. (Springer-Verlag, 2000)
The interfacing of digital image acquisition modalities to the picture archiving and communication system (PACS) plays a major part in the conversion from a traditional film-based radiology practice to one that relies almost entirely on soft-copy reading. The Baltimore Veterans Affairs Medical Center (VAMC) is one of the first filmless hospitals in the world. Since 1993, it has used computed tomography (CT) scanners connected to a commercial PACS to provide digitized patient images for filmless reading. Over the years, the evolution of Digital Imaging and Communications in Medicine (DICOM) standards, advances in networking technologies, and enhancements in PACS and hospital information system (HIS) software have greatly improved this system’s robustness and patient/study identification accuracy. The result has been a major increase in productivity.